10 Gbps Externally Modulated XGM Based Wavelength Conversion Using SOA. (2016) - Kappen, Minni J.; Asha, R.S.; Binesh, T.
Abstract: This paper proposes a method for All Optical Wavelength Conversion using semiconductor optical amplifier at 10Gbps. The system is demonstrated for Cross Gain Modulation (XGM) process of SOA, which is the simplest wavelength conversion technique that takes the advantage of non linear gain suppression mechanism in SOA. The system performances are analyzed using Q factor and Extinction Ratio of the eye diagram. The input pump power is varied from 2 dBm to 5 dBm; also the extinction ratio of Mach-Zehnder modulator is varied from 30 dBm to 60 dBm. Maximum Q Factor of 11.86dB is obtained for a maximum output signal power 23.94 dBm. Minimum Q Factor obtained is 7.58dB for a minimum output signal power 23.15 dBm. The extinction ratio falls from 18.56dB to 16.63dB as the input conditions are varied.